Formação de professores de inglês no ensino remoto emergencial: experiências e percepções de licenciandos sobre o estágio supervisionado - Maria Augusta de Matos Cruz (2021)
The present work sought to understand Brazilian undergraduate students’ impressions about their English Teaching Practicum course taught during the COVID-19 pandemic and its shift to the Emergency Remote Teaching (ERT). We understand that the study of teacher education in the context of the pandemic is of great relevance for the Applied Linguistics field, specially taking into account that it is an emergency and unprecedented teaching and learning experience that has created demands and unexpected challenges for both teachers and students. We of techniques and teaching methods (PENNYCOOK, 2004), but should also seek reflection on classroom choices (LEFFA, 2008) and produce knowledge focused on classroom practice, thus effecting a constant interaction between theory and practice (CELANI, 2008). We also acknowledge the Teaching Practicum as a space for interlocution and mutual learning among its participants (GIMENEZ; PEREIRA, 2007). Set on a qualitative approach, with an interpretive nature and an emic perspective, we used questionnaires, reflective diaries and semi-structured interviews with the participants of the research during their period of observation and intervention in schools, seeking to explore their perceptions on the Teaching Practicum and the ERT. The data generated was analyzed inductively (ERICKSON, 1986) in search of relevant topics. The results point to a change in the dynamics of interactions among the individuals involved in the course, in that case, although the ERT facilitated a greater interaction between student-teachers and in-service teachers, trainees who were unable to interact directly with school students showed concern with the lack of contact with those students. The participants also reveal a worrying overload of demands and responsibilities, which, in some cases, might culminate in student mental health issues.